The Phenomenon of Terrorism and Its International Repercussions Following The September 11, 2001 Attacks - Abdlnabi Ahmed Abdallah Salih; Abdlnabi Ahmed Abdallah Salih; Elbaghdadi Mohamed Saad (Journal of Scientific and Human Dimensions, 2025)
The attacks of September 11, 2001, marked a turning point in the global approach to terrorism. They prompted a redefinition of the security threat, recognizing transnational terrorist groups as a major strategic danger. Internationally, they led to the formation of a US-led global anti-terrorism coalition and the emergence of the concept of the "War on Terror." This resulted in direct military interventions, most notably the invasions of Afghanistan and Iraq, which reshaped the geopolitical landscape of the Middle East and Central Asia. The world also witnessed the adoption of stricter security legislation and strategies, focusing on enhancing intelligence and international security cooperation, but these also sparked debate about the balance between security and human rights. These transformations created a new international environment characterized by caution and the prominence of security considerations in relations between states.